A comparative study between input-output linearization control technique and backstepping control method for induction motor - Bùi Thị Kim Huệ; Mai Nhật Thiên; Lương Hoài Thương; Huỳnh Thị Dư; Ngô Bích Nên; Huỳnh Thanh Tường (Journal of Technical Education Science, 2021)
Three-phase induction motors are widely used in industry because of their advantages such as simple structure, solid, reliable operation, low maintenance and repairs, low-cost and high efficiency. However, the control of an induction motor is a difficult and complicated problem because of its strong nonlinearity. This paper applies the feedback linearization control technique (FLC) and the backstepping control method to design a control system for flux and speed for three-phase induction motor in which the torque and the flux are estimated from measurement of voltages and currents of the motor. The comparative of the motors components e.g. (flux, speed, torque and three-phase current) of the proposed FLC technique and Backstepping method is conducted. The comparison is carried out when changing the load on the motor shaft, the tracking capability of speed and the sensitivity when operating conditions are changed. The simulation results show the effectiveness of the proposed technique and method FLC.